A double-layer air electrode, a method for manufacturing the same, a double-layer air electrode half-cell, and a solid oxide cell
Patent Information
- Application Number
- CN202611172300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
本发明提供的双层空气极,一方面可以提高空气极功能层的通孔结构与三相位点数量,进而提升空气极的氧利用率与氧催化效率;另一方面,颗粒集电层在烧结过程中对纤维功能层起支撑保护作用,有利于提高整体固体氧化物电池的高温稳定运行性。
Smart Images

Figure CN122992089A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid oxide battery technology, specifically relating to a double-layer air electrode and its preparation method, a double-layer air electrode half-cell, and a solid oxide battery. Background Technology
[0002] Solid oxide cells (SOCs) are a type of all-solid-state electrochemical device with switchable functions. Their operating modes are mainly divided into two types: solid oxide fuel cells (SOFCs) for forward power generation and solid oxide electrolysis cells (SOECs) for reverse hydrogen / fuel production. Both have similar structures, comprising three key components: a fuel electrode, an electrolyte, and an air electrode. SOFCs, as highly efficient energy converters, can directly convert the chemical energy of hydrogen, ammonia, or hydrocarbons into electrical energy, with power generation efficiency far exceeding that of traditional heat engines, making them an important candidate technology for future distributed power generation. In recent years, with the advancement of "dual-carbon" goals, countries have focused more on the reverse mode of SOCs—SOECs: these utilize renewable electricity such as wind and solar power to electrolyze carbon dioxide and water into syngas (carbon monoxide + hydrogen), which can then be used to synthesize carbon-containing chemicals such as methanol and methane, and even directly produce hydrogen. This "electrochemical" coupling characteristic allows the same SOC equipment to both generate electricity and sequester carbon to produce fuel, making it one of the key technologies for energy transition.
[0003] The electrochemical processes on the surface of the air electrode in a State Activated Carbon (SOC) battery mainly include four sub-processes: oxygen adsorption / desorption, oxygen catalytic oxidation / reduction, oxygen ion conduction, and electron conduction. To improve the catalytic reaction rate and material conductivity, the operating temperature of an SOC battery stack is generally kept as high as possible. Taking a planar SOFC battery stack as an example, the operating environment of its air electrode is flowing air between 600-900℃. To ensure good structural stability and effective mass transfer at high temperatures, the air electrode material is generally a combination of ABO3-type perovskite and GDC (Gd-doped cerium oxide), and a pore-forming agent is added during the electrode fabrication process to form additional pore structures to enhance mass transfer.
[0004] Currently, most methods employ spherical or irregularly shaped perovskite powders as the air electrode material. For example, existing technologies have proposed a composite material with SSC-GDC coated with LSC perovskite structure, which, when used as the air electrode, can alleviate the thermal expansion mismatch and strontium segregation problems, thereby improving the thermal cycling performance of SOC batteries. However, these methods neglect the optimization of the air electrode pore structure, fail to address the mass transfer dead zone problem, and the underdeveloped pore structure limits the optimization effect of impregnation in these studies.
[0005] Existing technologies also disclose a nanofiber-like SSC as an air electrode framework, which improves the mismatch between the pore structure and thermal expansion coefficient of the air electrode, thereby reducing the polarization impedance of the SOC battery. However, the air electrode structure of the above methods is limited to a relatively low temperature condition of 650°C, and the stability problem of the fiber structure at higher temperatures has not been solved. Summary of the Invention
[0006] The purpose of this invention is to provide a double-layer air electrode and its preparation method, a double-layer air electrode half-cell, and a solid oxide battery.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a double-layer air electrode, comprising a stacked nanofiber layer and a porous particle layer; The nanofiber layer is made of La. x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 where 0 < x < 1, 0 < y < 1; The porous particle layer is made of La. z Sr 1-z CoO3, where 0 < z < 1; Chemical bonds are formed between the nanofiber layer and the porous particle layer.
[0008] Preferably, the thickness of the porous particle layer is 5~30μm; The particle size of the particles in the porous particle layer is 100~700nm; The pore size in the porous particle layer is 100~700nm.
[0009] Preferably, the thickness of the nanofiber layer is 5~30μm; The diameter of the fibers in the nanofiber layer is 100~200nm; The La x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 Ce y Gd 1-y O 1.95 The mass percentage content is 5-40%.
[0010] The present invention also provides a method for preparing the double-layer air electrode described in the above technical solution, comprising the following steps: Step 1: Mix nitrate, organic polymer solute, and organic solvent to obtain a spinning solution; the nitrate is La. x Sr1-x CoO3-Ce y Gd 1-y O 1.95 Nitrates corresponding to metal cations; Step 2: The spinning solution is subjected to electrospinning and calcination in sequence to obtain nanofibers; Step 3: After sequentially coating the nanofiber slurry and particle slurry on the substrate surface, calcination is performed to obtain the double-layer air electrode.
[0011] Preferably, in step 1, the concentration of metal cations in the spinning solution is 0.1~5 mol / L; The organic solvent includes at least one of dichloromethane, N,N-dimethylformamide, turpentine percolate, and dimethyl sulfoxide; the organic polymeric solute includes at least one of polyvinyl butyral, polyvinyl alcohol, polyvinylpyrrolidone, and ethyl cellulose. The viscosity of the spinning solution is 500~2000 mPa·s.
[0012] Preferably, the conditions for electrospinning include: a drum rotation speed of 300~800 rpm, an injection flow rate of 0.1~0.8 mL / h, a nozzle sweep speed of 10~40 mm / s, and a high voltage electric field strength of 1.0~2.0 kV / cm.
[0013] Preferably, in step 2, the calcination temperature is 800~1000℃, the holding time is 2~16h, and the heating and cooling rate is 1~10℃ / min.
[0014] Preferably, in step 3, the calcination temperature is 800~1000℃, the holding time is 2~16h, and the heating and cooling rate is 1~10℃ / min.
[0015] The present invention also provides a double-layer air electrode half-cell, comprising a barrier layer and an air electrode located on the surface of the barrier layer; The air electrode is a double-layer air electrode prepared by the above-described technical solution or by the preparation method described in the above-described technical solution.
[0016] The present invention also provides a solid oxide battery, wherein the cathode of the solid oxide battery is the double-layer air electrode described in the above technical solution or the double-layer air electrode prepared by the preparation method described in the above technical solution.
[0017] Compared with the prior art, the beneficial effects of the present invention include: The double-layer air electrode provided by this invention can, on the one hand, improve the through-pore structure and the number of three-phase points in the air electrode functional layer, thereby improving the oxygen utilization rate and oxygen catalytic efficiency of the air electrode; on the other hand, the particle current collector layer plays a supporting and protective role for the fiber functional layer during the sintering process, which is beneficial to improving the overall high-temperature stable operation of the solid oxide battery. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the double-layer air electrode half-cell structure of Example 1; Figure 2 This is a scanning electron microscope image of the multiphase nanofibers in Example 1; Figure 3 XRD patterns of the multiphase layer materials of Comparative Example 1 and Example 1; Figure 4 This is a scanning electron microscope image of the air electrode half-cell of Comparative Example 1. Figure 5 This is a scanning electron microscope image of the air electrode half-cell of Example 1; Figure 6 The graph shows the test results of the current-voltage characteristics of the full cell of Comparative Example 1 in Test Example 2 at 750~850℃; Figure 7 The graph shows the test results of the current-voltage characteristics of the full cell in Example 1 of Test Example 2 at 750~850℃; Figure 8 The graph shows the test results of the current-voltage characteristics of the full cell in Example 2 of Test Example 2 at 750~850℃; Figure 9 The graph shows the test results of the full cell of Comparative Example 2 at 750~850℃ for the current-voltage characteristics. Figure 10 The graph shows the test results of the full cells of Examples 1-2 and Comparative Examples 1-2 in Test Example 2 in co-electrolysis mode at a potential of 1.0-1.6V. Detailed Implementation
[0019] This invention provides a double-layer air electrode, comprising a stacked nanofiber layer and a porous particle layer; The nanofiber layer is made of La. x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 where 0 < x < 1, 0 < y < 1; The porous particle layer is made of La. z Sr 1-z CoO3, where 0 < z < 1; Chemical bonds are formed between the nanofiber layer and the porous particle layer.
[0020] In this invention, the thickness of the porous particle layer is preferably 5~30 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm. By limiting the thickness, the protection and support of the nanofiber layer by the particle layer is further ensured, and the electronic conduction resistance is reduced. Too small a thickness would result in insufficient protection of the nanofiber layer, easily leading to structural deterioration, breakage, and aggregation; while too large a thickness would cause the resistivity of the particle layer itself to increase with thickness.
[0021] In this invention, the particle size of the particles in the porous particle layer is preferably 100~700nm, specifically 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, or 700nm; the pore size of the porous particle layer is preferably 100~700nm, specifically 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, or 700nm; the above particle size and pore size ranges are beneficial for balancing the supporting strength and oxygen diffusion efficiency of the particle layer.
[0022] In this invention, the La z Sr 1-z CoO3 and La x Sr 1-x The CoO3 layers are not entirely identical, meaning the values of x and z are not exactly the same. The particle layer serves both a current collection and protection function, effectively preventing direct contact between the nanofiber structure and the conductive metal mesh. Combined with the above-mentioned nanofiber layer design, the overall air electrode possesses both the excellent electrochemical performance of the nanofiber layer and the high-temperature structural stability of the particle layer, thus facilitating the efficient operation of the solid oxide battery under high-temperature conditions.
[0023] In this invention, the thickness of the nanofiber layer is preferably 5-30 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm. This thickness limitation further balances the reactive region and impedance of the nanofiber layer. It avoids situations where the thickness is too small, resulting in insufficient reactive region and decreased electrochemical performance; and where the thickness is too large, causing the nanofiber layer's own resistance to increase with thickness.
[0024] In this invention, the diameter of the fibers in the nanofiber layer is preferably 100~200nm; limiting it to the above diameter avoids that if the diameter is too small, the strength of the nanofibers will be insufficient, which will easily cause the nanofiber layer structure to become unstable; and if the diameter is too large, the specific surface area of the nanofiber layer will be insufficient.
[0025] In this invention, the La x Sr 1-x CoO3-Ce y Gd 1-yO 1.95 Ce y Gd 1-y O 1.95 The preferred mass percentage content is 5-40%, specifically 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40%. These content limits are to avoid situations where the content is too low, resulting in low oxygen ion conductivity of the nanofibers and an increase in nanofiber layer impedance; or where the content is too high, resulting in low electronic conductivity of the nanofibers and an increase in nanofiber layer impedance.
[0026] In this invention, a multiphase fiber layer is employed. Compared to traditional particle packing morphology, the nanofiber structure design significantly enhances mass transfer and oxygen adsorption / desorption in the reaction zone of this layer, while avoiding additional impedance caused by phase interface inhomogeneity. Furthermore, this layer utilizes La... x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 (0 < x < 1, 0 < y < 1) perovskite material ensures oxygen ion conduction efficiency of the air electrode at 850℃.
[0027] The present invention also provides a method for preparing the double-layer air electrode described in the above technical solution, comprising the following steps: Step 1: Mix nitrate, organic polymer solute, and organic solvent to obtain a spinning solution; the nitrate is La. x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 Nitrates corresponding to metal cations; Step 2: The spinning solution is subjected to electrospinning and calcination in sequence to obtain nanofibers; Step 3: After sequentially coating the nanofiber slurry and particle slurry on the substrate surface, calcination is performed to obtain the double-layer air electrode.
[0028] Step 1 of this invention involves mixing nitrate, organic polymer solute, and organic solvent to obtain a spinning solution; the nitrate is La. x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 The nitrate corresponding to the metal cation.
[0029] In this invention, the nitrate preferably includes lanthanum nitrate hexahydrate, anhydrous strontium nitrate, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and gadolinium nitrate hexahydrate. In this invention, the organic solvent preferably includes at least one of dichloromethane, N,N-dimethylformamide, turpentine perol, and ethyl acetate; the above organic solvents can dissolve organic polymeric solutes and complex with metal cations, improving the phase formation quality of nanofibers; the organic polymeric solute preferably includes at least one of polyvinyl butyral, polyvinyl alcohol, polyvinylpyrrolidone, and ethyl cellulose; the polymeric solute is soluble in the organic solvent of the spinning solution and provides a suitable viscosity, improving the electrospinning effect. In this invention, the concentration of metal cations in the spinning solution is 0.1~5 mol / L, specifically 0.1 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, and 5.0 mol / L. These concentration limits prevent excessively high concentrations, which could lead to excessive electric field forces on the spinning solution and discontinuous fiber production; and excessively low concentrations, which could increase the dripping of the spinning solution.
[0030] In this invention, the organic polymer solute preferably accounts for 10-15 wt% of the spinning solution by mass, specifically 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%. In this invention, the viscosity of the spinning solution is preferably 500-2000 mPa·s, specifically 500 mPa·s, 1000 mPa·s, 1200 mPa·s, 1500 mPa·s, or 2000 mPa·s. These viscosity limitations prevent excessively high viscosity, which would result in excessive surface tension and coarse nanofibers, and excessively low viscosity, which would prevent the spinning solution from forming filaments.
[0031] In this invention, the mixing preferably includes: dissolving nitrate in an organic solvent by stirring, then adding an organic polymer solute and continuing to stir; the stirring speed is preferably 300 rpm and the stirring time is preferably 24 h.
[0032] After obtaining the spinning solution, step 2 of the present invention involves sequentially electrospinning and calcining the spinning solution to obtain nanofibers.
[0033] In this invention, the preferred conditions for electrospinning include: a drum rotation speed of 300~800 rpm (specifically, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, or 800 rpm), an injection flow rate of 0.1~0.8 mL / h (specifically, 0.1 mL / h, 0.2 mL / h, 0.3 mL / h, 0.4 mL / h, 0.5 mL / h, 0.6 mL / h, 0.7 mL / h, or 0.8 mL / h), a nozzle sweeping speed of 10~40 mm / s (specifically, 10 mm / s, 20 mm / s, 30 mm / s, or 40 mm / s), and a high-voltage electric field strength of 1.0~2.0 kV / cm (specifically, 1.0 kV / cm, 1.2 kV / cm, 1.5 kV / cm, 1.8 kV / cm, or 2.0 kV / cm). In this invention, the preparation of multiphase nanofiber materials by electrospinning is beneficial for precise control of the morphology and physical parameters of the nanofiber materials, ensuring the acquisition of nanofibers with the target phase and structural parameters. The preferred electrospinning process in this invention is as follows: preparing the spinning solution, selecting a nozzle as the high-voltage negative electrode and a rotating drum as the high-voltage positive electrode, inputting parameters into the electrospinning machine and starting the spinning program to obtain a fiber precursor, removing the fiber precursor from the rotating drum, folding it, placing it in a crucible, and calcining it to obtain multiphase nanofibers; wherein, before starting the spinning program, a layer of release paper can be attached to the rotating drum to facilitate the collection of the fiber precursor after spinning.
[0034] In this invention, multiphase nanofibers are prepared by electrospinning, which facilitates the control of the phase ratios and fiber diameters within the multiphase nanofibers, ensuring the acquisition of multiphase nanofibers with optimal performance parameters. The electric field strength refers to the ratio of the potential difference between the high-voltage positive and negative electrodes to the distance between the two electrodes, measured as the distance between the nozzle tip and the drum surface. This avoids situations where the electric field strength is too high, resulting in excessively thin nanofibers, or too low, preventing the spinning solution from forming fibers.
[0035] In this invention, the calcination temperature is preferably 800~1000℃, specifically 800℃, 900℃, or 1000℃; the holding time is preferably 2~16h, specifically 2h, 4h, 6h, 8h, 10h, 12h, 14h, or 16h; the heating and cooling rate is preferably 1~10℃ / min (i.e., after calcination, a cooling process is also included), specifically 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min; the calcination is preferably carried out in an air atmosphere. In this invention, through the above heating and cooling process, uniformly formed and tough multiphase nanofibers can be obtained, further enhancing the high-temperature stability of the multiphase nanofibers, enabling them to withstand the thermal and mechanical stresses of the battery working environment.
[0036] After obtaining the nanofibers, step 3 of the present invention involves sequentially coating the nanofiber slurry and the particulate slurry onto the substrate surface and then calcining them to obtain the double-layer air electrode.
[0037] In this invention, the nanofiber slurry preferably comprises nanofibers, an organic polymer solute, and an organic solvent. The types of the organic polymer solute and organic solvent are consistent with those in the above-described technical solutions and will not be repeated here. In this invention, the total mass of the organic polymer solute and organic solvent (collectively referred to as binder) in the nanofiber slurry preferably accounts for 10-70%, specifically 10%, 20%, 30%, 40%, 50%, 60%, or 70%; this avoids excessive binder, which would make the slurry too thin and difficult to coat, and insufficient binder, which would make the slurry too thick.
[0038] In this invention, the granular slurry preferably includes La. z Sr 1-z The invention comprises CoO3 powder, a pore-forming agent, an organic polymeric solute, and an organic solvent. In this invention, the pore-forming agent is preferably PMMA microspheres, and the particle size of the pore-forming agent is preferably 100-700 nm, specifically 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, or 700 nm. The mass percentage of the pore-forming agent in the granular slurry is preferably 5-10 wt%, specifically 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%. In this invention, the types of the organic polymeric solute and organic solvent are consistent with those in the above-mentioned technical solutions and will not be repeated here. In this invention, the total mass percentage of the organic polymeric solute and organic solvent in the granular slurry is preferably 10-70%, specifically 10%, 20%, 30%, 40%, 50%, 60%, or 70%.
[0039] The present invention does not impose any special limitations on the coating process; any process well known to those skilled in the art can be used.
[0040] In this invention, the calcination temperature is preferably 800~1000℃, specifically 800℃, 900℃, or 1000℃; the holding time is preferably 2~16h, specifically 2h, 4h, 6h, 8h, 10h, 12h, 14h, or 16h; the heating and cooling rate is preferably 1~10℃ / min, specifically 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min; the calcination is preferably carried out in an air atmosphere. In this invention, during the calcination process, the particle layer and the nanofiber layer are tightly bonded to form a double-layer air electrode, thereby ensuring the mass transfer advantage of the fiber structure at 850℃ while inhibiting the deterioration of the fiber structure, resulting in good electrochemical performance and high-temperature structural stability.
[0041] The present invention also provides a double-layer air electrode half-cell, comprising a barrier layer and an air electrode located on the surface of the barrier layer; The air electrode is a double-layer air electrode prepared by the above-described technical solution or by the preparation method described in the above-described technical solution.
[0042] In this invention, the material of the barrier layer is preferably Ce. y Gd 1-y O 1.95 (0 < y < 1); the thickness of the barrier layer is preferably 5~10 μm.
[0043] The present invention also provides a solid oxide battery, wherein the cathode of the solid oxide battery is the double-layer air electrode described in the above technical solution or the double-layer air electrode prepared by the preparation method described in the above technical solution.
[0044] In this invention, the solid oxide battery preferably includes a solid oxide fuel cell (SOFC) and a solid oxide electrolyzer (SOEC); in the SOFC, the double-layer air electrode is responsible for the reduction reaction of oxygen, where oxygen molecules gain electrons and are converted into oxygen ions; in the SOEC, the double-layer air electrode is the site of oxygen evolution, where oxygen ions lose electrons to generate oxygen and undergo an oxidation reaction.
[0045] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0046] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0047] Example 1 Preparation of spinning solution: Weigh 2.79 g of lanthanum nitrate hexahydrate, 0.91 g of anhydrous strontium nitrate, 3.12 g of cobalt nitrate hexahydrate, 2.06 g of cerium nitrate hexahydrate, and 0.54 g of gadolinium nitrate hexahydrate into a clean beaker, then add 100 mL of N,N-dimethylformamide and stir until all the solids are dissolved; weigh 17.2 g of the above solution into a clean beaker, add 2.8 g of polyvinylpyrrolidone, and stir magnetically for 24 h at 300 rpm to obtain the spinning solution (viscosity 1200 mPa·s). Electrospinning: The spinning solution was placed in an injection pump, and the injection flow rate was set to 0.5 mL / h. The high-voltage negative electrode of the injection pump nozzle was connected, and the negative electrode high voltage was set to -2 kV. The nozzle sweeping speed was set to 20 mm / s. A layer of release paper was attached to the drum, and the drum rotation speed was set to 300 rpm. The high voltage of the drum positive electrode was set to 19 kV. The vertical distance between the nozzle and the drum surface was adjusted to 15 cm. The electrospinning machine was set to operate for 4 hours. After spinning, the fiber precursor film was removed from the release paper, folded, and placed in a crucible. It was calcined in an air atmosphere at 800℃ for 2 hours with a heating / cooling rate of 1℃ / min to obtain La. 0.6 Sr 0.4 CoO3-Ce 0.8 Gd 0.2 O 1.95 Multiphase nanofibers (of which Ce8Gd2O) 1.95 (The mass percentage is 30 wt%, and the diameter is 200 nm). Preparation of a double-layer air electrode half-cell: La6Sr4CoO3 powder, La6Sr4CoO3-Ce8Gd2O 1.95 Multiphase nanofibers were separately prepared into slurries; The granular slurry includes La6Sr4CoO3 powder, PMMA microspheres (5.6 wt% content, 500 nm particle size), organic solvent, and organic polymer solute. The organic solvent is ethyl acetate, the organic polymer solute is ethyl cellulose, and the binder has a mass percentage of 45 wt%. The organic solvent in the nanofiber slurry is ethyl acetate, the organic polymer solute is ethyl cellulose, and the binder has a mass percentage of 56 wt%. Figure 1 The coatings are applied sequentially to barrier layer 3 (specifically, the material is Ce). 0.8 Gd0.2 O 1.95 The battery was then calcined in an air atmosphere at 900℃ for 2 hours at a heating / cooling rate of 3℃ / min, resulting in a double-layer air electrode half-cell. The particle layer was 20μm thick, with particle size and pore size conforming to a normal distribution (particle size 100~700nm, pore size 100~700nm); the fiber layer was 30μm thick. A schematic diagram of the specific structure is shown below. Figure 1 As shown, 1-particle layer, 2-nanofiber layer, 3-barrier layer).
[0048] Example 2 Preparation of spinning solution: Weigh 2.79 g of lanthanum nitrate hexahydrate, 0.91 g of anhydrous strontium nitrate, 3.12 g of cobalt nitrate hexahydrate, 2.06 g of cerium nitrate hexahydrate, and 0.54 g of gadolinium nitrate hexahydrate into a clean beaker, then add 100 mL of N,N-dimethylformamide and stir until all the solids are dissolved; weigh 18 g of the above solution into a clean beaker, add 2.0 g of polyvinylpyrrolidone and stir magnetically for 24 h at 300 rpm to obtain the spinning solution (viscosity 900 mPa·s). Electrospinning: The spinning solution was placed in an injection pump, and the injection flow rate was set to 0.5 mL / h. The high-voltage negative electrode of the injection pump nozzle was connected, and the negative electrode high voltage was set to -2 kV. The nozzle sweeping speed was set to 20 mm / s. A layer of release paper was attached to the drum, and the drum rotation speed was set to 300 rpm. The high voltage of the drum positive electrode was set to 19 kV. The vertical distance between the nozzle and the drum surface was adjusted to 15 cm. The electrospinning machine was set to operate for 4 hours. After spinning, the fiber precursor film was removed from the release paper, folded, and placed in a crucible. It was calcined in an air atmosphere at 800℃ for 2 hours with a heating / cooling rate of 1℃ / min to obtain La. 0.6 Sr 0.4 CoO3-Ce 0.8 Gd 0.2 O 1.95 Multiphase nanofibers (of which Ce8Gd2O) 1.95 (The mass percentage is 30 wt%, and the diameter is 120 nm). A double-layer air electrode half-cell was prepared according to Example 1.
[0049] Comparative Example 1 La6Sr4CoO3 powder, La6Sr4CoO3-Ce8Gd2O 1.95 After the multiphase particles were prepared into slurries (see Example 1 for preparation method), they were then... Figure 1 The La6Sr4CoO3 particles are sequentially coated onto barrier layer 3 in the order shown. The thickness of the La6Sr4CoO3 particle layer is 20 μm. 1.95The thickness of the multiphase particle layer is 30 μm. The battery is then calcined in an air atmosphere at a temperature of 900 °C for 2 hours with a heating / cooling rate of 3 °C / min to obtain a double-layer air electrode half-cell.
[0050] Comparative Example 2 Preparation of spinning solution: Weigh 2.79g of lanthanum nitrate hexahydrate, 0.91g of anhydrous strontium nitrate, 3.12g of cobalt nitrate hexahydrate, 2.06g of cerium nitrate hexahydrate, and 0.54g of gadolinium nitrate hexahydrate into a clean beaker, then add 100mL of N,N-dimethylformamide and stir until all the solids are dissolved; weigh 16.4g of the above solution into a clean beaker, add 3.6g of polyvinylpyrrolidone, and stir magnetically for 24h at 300rpm to obtain the spinning solution (viscosity 1500mPa·s). Electrospinning: The spinning solution was placed in an injection pump, and the injection flow rate was set to 0.5 mL / h. The high-voltage negative electrode of the injection pump nozzle was connected, and the negative electrode high voltage was set to -2 kV. The nozzle sweeping speed was set to 20 mm / s. A layer of release paper was attached to the drum, and the drum rotation speed was set to 300 rpm. The high voltage of the drum positive electrode was set to 19 kV. The vertical distance between the nozzle and the drum surface was adjusted to 15 cm. The electrospinning machine was set to operate for 4 hours. After spinning, the fiber precursor film was removed from the release paper, folded, and placed in a crucible. It was calcined in an air atmosphere at 800℃ for 2 hours with a heating / cooling rate of 1℃ / min to obtain La. 0.6 Sr 0.4 CoO3-Ce 0.8 Gd 0.2 O 1.95 Multiphase nanofibers (of which Ce8Gd2O) 1.95 (The mass percentage is 30 wt%, and the diameter is 300 nm). A double-layer air electrode half-cell was prepared according to Example 1.
[0051] Performance testing Test Example 1 Figure 2 The image shows a scanning electron microscope image of the multiphase nanofibers obtained in Example 1; it can be seen that the calcined fibers have a uniform morphology and a very high specific surface area. Figure 3 The XRD patterns of the multiphase layer materials in Comparative Example 1 and Example 1 show that the fiber powder has a more uniform phase composition and fewer impurities. Figure 4 This is a cross-sectional scanning electron microscope image of the air electrode half-cell of Comparative Example 1. Figure 5 This is a scanning electron microscope image of the air electrode half-cell of Example 1; from Figure 4 and 5It can be seen that the nanofiber layer has more developed pores than the particle layer in the comparative example, and the fiber morphology is effectively protected by the outer current-collecting particle layer.
[0052] Test Example 2 To test the performance of the double-layer air electrode, the half-cell was assembled into a full cell for electrochemical performance testing. The full cell adopted an electrolyte-supported configuration, with the electrolyte being a 90 μm thick 3YSZ sheet. The fuel electrode side used a classic Ni-GDC electrode with an electrode area of 0.5 cm². 2 The electrode thickness is 25 μm. All comparative examples and full cells differ only in the air electrode half-cell; the fuel electrode remains the same. Figure 6 The graph shows the test results of the current-voltage characteristics of the full cell in Comparative Example 1 at 750~850℃. Figure 7 , 8 Figures 9 and 1 are the test results of the current-voltage characteristics of the full cells of Examples 1 and 2 and Comparative Example 2 at 750~850℃, respectively. Figure 10 The graph shows the test results of the full cells of Comparative Examples 1-2 and Examples 1-2 in co-electrolysis mode at a potential of 1.0-1.6V. Depend on Figures 6-10 It can be known that: The power density of Comparative Example 1 increases with increasing temperature in the 750~850℃ temperature range, and the electrolysis current density in the 1.0~1.6V electrolysis mode increases with increasing potential, which is consistent with the basic characteristics of LSC-CGO air-electrode solid oxide fuel cells. Examples 1 and 2 of this invention have higher power density and electrolysis current density compared to Comparative Examples 1 and 2, as shown in Tables 1 and 2.
[0053] Table 1 Maximum power density of the full cell (W / cm³) 2 )
[0054] Table 2 Electrolysis current density of the full cell (A / cm²) 2 )
[0055] Taking Example 1 as an example, its power density is higher than that of Comparative Example 1 in the temperature range of 750~850℃, with the power density reaching 0.52W / cm² at 850℃. 2 This represents a 26.8% improvement compared to Comparative Example 1; the electrolysis current density in the 1.0~1.6V range is higher than that of Comparative Example 1, with the electrolysis current density reaching 1.56 A / cm² at 1.6V. 2 This represents an 18.2% increase compared to control group 1. Combined with... Figure 2 , Figure 3 and Figure 4As shown, the composite fiber layer of the embodiment is well bonded to the particle layer and the barrier layer, and the effective pore density is much higher than that of the composite particle layer in the comparative example, which significantly enhances the mass transfer process of the air electrode and reduces the polarization impedance. The particle layer outside the composite fiber layer protects the short fibers and ensures that the composite fiber layer does not fail or deform at 850°C. The fiber structure suppresses the segregation of Ce element to a certain extent. The composite fiber layer of the embodiment has a purer phase and a lower ohmic impedance.
[0056] In summary, the bilayer air electrode of this invention possesses excellent electronic and oxygen ion conductivity, superior mass transfer performance, resistance to high-temperature oxidizing atmospheres, structural stability, and low contact resistance, and is compatible with both FC and EC operating modes. Furthermore, the multiphase nanofiber material exhibits pure phase formation, well-developed pores, and is suitable for various applications; its synthesis is simple, and the raw materials are abundant and readily available.
[0057] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A double-layer air electrode, characterized in that, It includes a layered nanofiber layer and a porous particle layer; The nanofiber layer is made of La. x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 where 0 < x < 1, 0 < y < 1; The porous particle layer is made of La. z Sr 1-z CoO3, where 0 < z < 1; Chemical bonds are formed between the nanofiber layer and the porous particle layer.
2. The double-layer air electrode according to claim 1, characterized in that, The thickness of the porous particle layer is 5~30μm; The particle size of the particles in the porous particle layer is 100~700nm; The pore size in the porous particle layer is 100~700nm.
3. The double-layer air electrode according to claim 1, characterized in that, The thickness of the nanofiber layer is 5~30μm; The diameter of the fibers in the nanofiber layer is 100~200nm; The La x Sr 1-x CoO3-Ce y Gd 1-y O 1.95 Ce y Gd 1-y O 1.95 The mass percentage content is 5-40%.
4. The method for preparing the double-layer air electrode according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step 1: Mix nitrate, organic polymer solute, and organic solvent to obtain a spinning solution; the nitrate is La. x Sr 1- x CoO3-Ce y Gd 1-y O 1.95 Nitrates corresponding to metal cations; Step 2: The spinning solution is subjected to electrospinning and calcination in sequence to obtain nanofibers; Step 3: After sequentially coating the nanofiber slurry and particle slurry on the substrate surface, calcination is performed to obtain the double-layer air electrode.
5. The preparation method according to claim 4, characterized in that, In step 1, the concentration of metal cations in the spinning solution is 0.1~5 mol / L; The organic solvent includes at least one of dichloromethane, N,N-dimethylformamide, turpentine percolate, and dimethyl sulfoxide; the organic polymeric solute includes at least one of polyvinyl butyral, polyvinyl alcohol, polyvinylpyrrolidone, and ethyl cellulose. The viscosity of the spinning solution is 500~2000 mPa·s.
6. The preparation method according to claim 4, characterized in that, The conditions for electrospinning include: a drum rotation speed of 300~800 rpm, an injection flow rate of 0.1~0.8 mL / h, a nozzle sweep speed of 10~40 mm / s, and a high voltage electric field strength of 1.0~2.0 kV / cm.
7. The preparation method according to claim 4, characterized in that, In step 2, the calcination temperature is 800~1000℃, the holding time is 2~16h, and the heating and cooling rate is 1~10℃ / min.
8. The preparation method according to claim 4, characterized in that, In step 3, the calcination temperature is 800~1000℃, the holding time is 2~16h, and the heating and cooling rate is 1~10℃ / min.
9. A double-layer air electrode half-cell, characterized in that, Includes a barrier layer and an air electrode located on the surface of the barrier layer; The air electrode is a double-layer air electrode as described in any one of claims 1 to 3 or a double-layer air electrode prepared by the preparation method described in any one of claims 4 to 8.
10. A solid oxide battery, characterized in that, The cathode of the solid oxide battery is the double-layer air electrode as described in any one of claims 1 to 3 or the double-layer air electrode prepared by the preparation method described in any one of claims 4 to 8.